Markers of structural and cellular renal damage in localized renal cell carcinoma before treatment - E. M. Frantsiyants; N. D. Ushakova; D. A. Rozenko; N. N. Popova; A. D. Rozenko; A. V. Shulga (Южно-Российский онкологический журнал, 2022)
Purpose of the study. The purpose of the study was to analyze parameters of molecular markers of structural and cellular renal damage in localized renal cell carcinoma (RCC) with determining the nature of the initial abnormalities in the kidney functional state before the treatment.Patients and methods. The study included 46 patients receiving elective surgical treatment for localized renal cancer in the Department of Oncourology, National Medical Research Centre for Oncology. The comparison group included the clinical and laboratory data of 13 healthy people comparable with the RCC patients in terms of age and gender. Cystatin C, IL‑18, KIM‑1, L-FABP, NGAL were determined in blood and urine in all patients.Results. Evaluation of the kidney functional state of RCC patients showed that the initial values of serum creatinine and the glomerular filtration rate were similar to the reference levels in healthy people, but statistically significant differences were found in the ratios of cystatin C concentrations in the blood and urine in all patients, compared with normal values. Determination of L-FABP indices in RCC patients showed that their levels were 2.5 times higher than normal values, and the urine concentration of IL‑18 was 1.7 times higher than normal values (p < 0.05). Blood and urine levels of NGAL and KIM‑1 did not differ significantly from the comparison group.Conclusions. The development of localized RCC is accompanied by the formation of tubulointerstitial dysfunction with impaired renal filtration capacity. All RCC patients showed elevated endogenous markers of structural and cellular renal damage – cystatin C, L-FABP, and IL‑18.